ICT4Ag Internship Experiences - Bappa Se, Marc Ghislain (Technical Centre for Agricultural and Rural Cooperation, 2018)
Marc Ghislain Bappa Se, ICT4Ag intern at CTA, shares how he has been involved in the organisation of the Pitch-Agrihack competition and the knowledge he has acquired during his internship.